2019
DOI: 10.1002/aoc.5113
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated ZnMoO4 photocatalytic degradation of pirimicarb under UV light mediated by peroxymonosulfate

Abstract: This paper reports the optimized synthesis of zinc molybdates by the hydrothermal method and the combination of ZnMoO4 and peroxymonosulfate (PMS) under UV irradiation for the degradation of pirimicarb. The as‐prepared ZnMoO4 photocatalyst was characterized using X‐ray diffraction, scanning electron microscopy, X‐ray photoelectron spectroscopy and UV–visible diffuse reflectance spectroscopy. The effects of operational parameters in the ZnMoO4/PMS/UV system were evaluated and the results indicated the highest p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 68 publications
1
15
0
Order By: Relevance
“…In addition, it was observed that different shapes were obtained by tuning E surf for β-ZnMoO 4 , such as truncated and nontruncated rectangular, hexagonal, octahedral, and rhombic shapes matching the experimental morphologies obtained by examining the FE-SEM images. 64,67,69,71,88 These experimentally observed morphologies should be close to the equilibrium shapes under the experimental conditions. From a thermodynamic point of view, the morphology is controlled by relative stability of different surfaces, and the surface with the lowest E surf value is the main component of the corresponding morphology.…”
Section: Journal Of Applied Physicssupporting
confidence: 68%
See 2 more Smart Citations
“…In addition, it was observed that different shapes were obtained by tuning E surf for β-ZnMoO 4 , such as truncated and nontruncated rectangular, hexagonal, octahedral, and rhombic shapes matching the experimental morphologies obtained by examining the FE-SEM images. 64,67,69,71,88 These experimentally observed morphologies should be close to the equilibrium shapes under the experimental conditions. From a thermodynamic point of view, the morphology is controlled by relative stability of different surfaces, and the surface with the lowest E surf value is the main component of the corresponding morphology.…”
Section: Journal Of Applied Physicssupporting
confidence: 68%
“…In the case of β-ZnMoO 4 , a series of experimental works have been developed in order to elucidate the shape-dependent properties of the monoclinic wolframite material, especially in the photoluminescence and photocatalysis fields. 64,67,69,71,88 However, the reasons behind the shape-dependent properties remain unclear, with the combination of theory and simulation being an alternative tool in this research area that can guide the efficient synthesis of outstanding materials. The Wulff construction was employed in this study in order to rationalize the crystal morphologies, which is related to the relative stability of the exposed surfaces.…”
Section: B Crystal Morphologymentioning
confidence: 99%
See 1 more Smart Citation
“…The main factor in assessment of the photocatalytic activity of a semiconductor is its optical absorption properties, which depend on its band structure [ 34 , 35 , 36 ]. Thus, the UV–vis diffuse reflectance spectrum of SnIn 4 S 8 was recorded ( Figure 3 a).…”
Section: Resultsmentioning
confidence: 99%
“…Among the different hybridized boron reagents employed in SMCs (e.g., aryl, heteroaryl, and vinylboronic acids and esters), the use of organoboron compounds with alkyl groups (sp 3 carbon) was severely limited in these coupling reactions due to competitive side reactions [39,40]. Organometallic compounds that are metalated at sp 3 Metal catalysis has had a major impact on numerous research fields from energy, biomass, environmental and water purification to synthesis of otherwise challenging and even inaccessible materials and medicinal adducts [18][19][20][21][22][23][24][25][26][27][28][29][30]. In line, the intensive research in metal catalysis has led to significant progress in borylation of primary C(sp 3 )-H bonds of unfunctionalized hydrocarbons, allowing access to a variety of C(sp 3 )-B reagents and consequent breakthroughs in C(sp 3 )-C(sp,sp 2 ,sp 3 ) cross-couplings.…”
Section: Introductionmentioning
confidence: 99%